Croton crossolepis (Euphorbiaceae), a new species with an unusual trichome type from southwestern Madagascar - E. Berry, Paul; Kainulainen, Kent (Phytotaxa, 2017)
Croton crossolepis is newly described and illustrated. It is a shrub or small tree endemic to southwestern Madagascar near Toliara and is distinguished by a mixture of stellate and lepidote trichomes, with most of the lepidote ones having fringed margins and partially free, stiff rays that can make it adhere to surfaces like clothing when they come into contact. The inflorescences are pseudoterminal and spicate in appearance, with numerous flowers subtended by acicular bracts that are longer than the buds. It has larger leaves than most Croton species that occur in the semi-arid southwestern scrub and spiny forests nearby in the country, and it is apparently quite rare and subject to ongoing decline, warranting a conservation assessment of Vulnerable.